Pengaruh Influencer Marketing dan Viral Marketing Terhadap Keputusan Pembelian - Nadifa Ariya Maulinda; Slamet (Masyarakat Ekonomi Syariah Bogor, 2025)
Purchase decisions are the primary goal of marketing, impacting a company's profitability through increased sales. The decision-making process is often influenced by external factors. Therefore, marketers need to understand the driving factors behind consumer preferences and provide information to reduce the risk of negative preferences. The rapid development of electronic media, particularly social media, facilitates easier access to information. Marketing strategies such as influencer marketing and viral marketing are used to expand the reach of product information. This study aims to examine the influence of influencer marketing and viral marketing on the purchase decision of Azarine sunscreen products in Malang City. This research uses a qualitative approach. The object of this study is Azarine sunscreen and its consumers as subjects, with an unknown probability category of population selection. The sampling technique used is purposive sampling. A total of 104 respondents in Malang City were obtained as samples. The research data was collected through a survey using a Likert-scale questionnaire distributed directly to the respondents. The data will be analyzed using descriptive analysis techniques and SmartPLS version 4 statistics. The results of this study indicate that: (1) Influencer marketing has a significant positive effect on the purchase decision of Azarine sunscreen products. (2) Viral marketing has a significant positive effect on the purchase decision of Azarine sunscreen products.